London Bulletin (eerste nummer : London Gallery Bulletin) - Mesens, Edouard Léon Theodore (London : The London Gallery, 1938)
London Bulletin was a magazine edited by E.L.T. Mesens and published by London Gallery in London in 20 numbers between April 1938 and June 1940.The magazine had been the most influential English Surrealist periodical. Each issue published had different colour wrappers and titles in various colours with varying number of pages, although the size 250 x 190 mm was consistent. Although it described itself as an avant-garde review, Surrealist contributions predominated; the periodical also featured Constructivism and more abstract art. Contributors included Paul Eluard, Herbert Read, E.L.T. Mesens, André Breton, Nash, Tanguy, Samuel Beckett, Peret, Francis Picabia, George Reavey, Humphrey Jennings, Roland Penrose, Eileen Agar, John Banting, Conroy Maddox and many others (monoskop.org)
Online: https://monoskop.org/London_Bulletin
Engels
Tijdschriften
Keywords: Mesens, Edouard Léon Theodore; surrealisme; avant-garde.